Knowledge through communication : a response to the question of how testimony-based knowledge is possible - Dewhurst, Thérèse (Department of Philosophy, 2015)
The aim of this thesis is to offer a response to the question of how it is that a hearer can get knowledge from testimony. The project has two main components. The first is to suggest that the obstacle to getting knowledge through testimony (the obstacle of epistemic vulnerability) is one that can be ignored. The second is to set out how it is that mere communication could be sufficient to explain how testimony can be a source of knowledge. The first component constitutes a proposal to reject the problem of testimony as it is usually conceived. Testimony is often seen to be epistemically distinct and interesting because of the apparent epistemic vulnerability posed by its being an indirect source of knowledge. Viewing the problem in this way has led most epistemologists to set out on a project of justification: the challenge is to explain how it is that hearing an assertion can be sufficient grounds for coming to know what is asserted. Whether one is a reductionist or a non-reductionist, the aim has been to establish that essential link between hearing a speaker assert that p, and p's being true. I will argue that seeing the problem of testimony as one of epistemic vulnerability is only inevitable if one has a particular view of knowledge. If we take knowledge to be a state metaphysically distinct from belief, a state not dependent on its justification to establish it as knowledge, then the indirectness of testimony does not inevitably result in a problem of vulnerability. The second component constitutes a positive explanation for the possibility of knowledge through testimony. I argue that (rather than seeking to justify our testimony-based beliefs) we ought to try to understand the mechanism whereby knowledge can be made available to a hearer simply by understanding an assertion. In this endeavour, I propose a certain theory of communication, such that understanding a communicative utterance entails coming to recognise the speaker's actual mental state. If successful communication gives the hearer access to the speaker's actual mental state, then successful communication can explain how understanding an assertion that p can get a hearer to know that p. I argue that correctly understanding an assertion that p entails coming to know that p. I defend the idea that the institution of communication explains how knowledge through testimony is possible.